THE EFFECTIVENESS OF SOMATIC AUDITORY VISUAL AND INTELECTUAL (SAVI) LEARNING APPROACH ASSISTED PROBLEM CARD TOWARDS THE STUDENTS’ LIVELINESS AND ACHIEVEMENT ON TRIGONOMETRY MATERIAL OF MATHEMATICS LEARNING - Wulan Maulida; Ponoharjo Ponoharjo; Wikan Budi Utami (MEJ (Mathematics Education Journal), 2017)
This study aimed to know if the X grade students of SMA Negeri 4 KotaTegal who were taught by using SAVI learning approach assisted problemcard were: (1) reach the learning target achievement, (2) there is a distinctionbetween students and the students who are taught by using SAVI learningapproach towards their liveliness and achievement, (3) the liveliness andachievement of students are better than the students who are taught by usingSAVI learning approach. The researcher conducted the study at SMA Negeri4 Kota Tegal in 2016/2017 academic year. The population under study was282 students. This study used quasi-experimental methodology whichconsisted of 61 students as the population sample. Cluster random samplingtechnique was used to determine the population sample. The Instruments ofthis study were observation on the students’ liveliness of mathematicslearning which had been passed validity testing by the expert and theachievement test of mathematic learning which had been passed validity andreliability testing. Furthermore, the researcher used proportion test, manovatest and T2-Hotteling test as the data analysis technique. The results of thestudy on the X grade students of SMA Negeri 4 Kota Tegal showed: (1) Thestudents who were taught by using SAVI learning approach assisted problemcard reached the target achievement, (2) there were differences between thestudents who were taught by using SAVI learning approach assisted problemcard and the students who were taught by using SAVI learning approach interms of students’ liveliness and achievement. (3) the liveliness andachievement of the students who were taught by using SAVI learningapproach assisted problem card were better than the students who were taughtby using SAVI learning approach.